The Fiscal Theory of the Price Level with a Bubble - Markus K. Brunnermeier; Sebastian Merkel; Yuliy Sannikov (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper incorporates a bubble term in the standard FTPL equation to explain why countries with persistently negative primary surpluses can have a positively valued currency and low inflation. It also provides an example with closed-form solutions in which idiosyncratic risk on capital returns depresses the interest rate on government bonds below the economy's growth rate.
Keywords: E44; E52; E63; 330